(untitled) (Revista Contexto & Educação, 2023)
It analyzes the pedagogical planning from the reality/present as a starting point in different theories/trends and deepens the proposal in the Marxist perspective. It assumes planning as a central element in the organization of pedagogical work. It explains two planning experiences in the Marxist perspective, historic critical pedagogy and complexes of study. Performs bibliographic and field research based on university extension programs and projects carried out by the authors in the context of the countryside and indigenous people in Parana. It highlights that the critical perspective of education, based on Marxism, assumes reality/present as the basis for school planning, there is the challenge of apprehending it dialectically as education of the working class. It evidences advances in the Landless Rural Workers Movement (MST) proposal and the planning in camp and settlement schools from the Complexes of Study. It emphasizes that in this experience, the actions of planning involve the intention of apprehending knowledge and training students to act in reality/present to overcome the oppression, exploitation and expropriation present in capitalist society. It concludes that the MST’s planning experience gives an ontological leap in its praxis when it incorporates the current category and gives a new meaning to the reality category, surpassing it by incorporation.